(untitled) (Quinto Sol, 2021)
The purpose of this article is to understand what place the representations of Marxism and the left occupied in Tacuara and its branch organizations, as part of a broader investigation of the Catholic, Marxist and nationalist groups identified with the Peronist left in the ‘60s. The text states that Marxism and the left were represented as a radical otherness with negative features, which operated as a constitutive exterior of the tacuarist identity itself. The conspiracy theory of universal government, or the cultural battle between Christianity and materialism, could not function without the specter of communism as a permanent and multiform threat. On the other hand, nationalist groups wanted to imitate the efficiency attributed to communism to infiltrate societies and colonize consciences. In this context, the concept of class struggle was problematized by Tacuara, and then incorporated by some of its subdivisions, which evidences the displacement of a culturalist nationalism to a more secularized one. To advance these formulations, will be analyzed the political press of Tacuara and its derivative groups, such as Tacuara. Vocero De La Juventud Nacionalista, Ofensiva, Barricada Del Nacionalismo Revolucionario, Tacuara del manchón y Nueva Argentina, among other documents.